Penggunaan Zeolite Sebagai Filter Untuk Menurunkan Emisi Gas Buang Berdasarkan Ukuran dan Tingkat Kejenuhan Absorsi: Use of Zeolite as a Filter to Reduce Exhaust Gas Emissions Based on Size and Absorption Saturation Level - Sirajuddin, Sirajuddin; Purnomo, Bagiyo Condro (Borobudur Engineering Review, 2024)
Motorized vehicles have become a fundamental necessity in Indonesia, with each household owning at least one motorcycle highly favored by the community. The increase in the number of motorcycles reflects the performance of the automotive industry and the continuous improvement of people's purchasing power. Despite contributing positively to economic growth and mobility, the growth of motorized vehicles also brings negative impacts such as traffic congestion, air pollution, and dependence on imported petroleum. Exhaust emissions from vehicles, containing CO2, NOx, CO, VHC, and other particles, have serious implications for human health and the environment. The initiative to use environmentally friendly transportation technology, as adopted by the European Union with Euro emission standards, is crucial in reducing these negative impacts. In Indonesia, the adoption of Euro 4 emission standards in 2018 for gasoline-fueled cars and in 2021 for diesel cars is a positive step, despite the delay for diesel cars until 2022. Previous research indicates that alternative fuels like LPG can reduce exhaust emissions. Additionally, using a filter in motorcycle mufflers, especially with zeolite as a medium, can effectively reduce CO and HC levels. However, there is no in-depth research on the saturation level of zeolite's absorption capacity for exhaust emissions. Therefore, this study focuses on exploring the saturation level of zeolite material with various sizes to absorb exhaust emissions, particularly HC, CO, and CO2 in motorized vehicles. The research results reveal that the optimal outcome for the saturation level of zeolite material absorption in the muffler filter of Yamaha Jupiter Z 110cc vehicles is achieved using 10 grams of zeolite powder with mesh size 50. The best CO concentration reduction occurs at 1000 rpm for 35 minutes, achieving a 66.9% reduction, reaching 2.85%. For HC, the best result is obtained in testing with 10 grams of zeolite powder mesh 50 at 1000 rpm for 20 minutes, with a 90.58% reduction, reaching 227 ppm. The optimal CO2 testing is conducted with 10 grams of zeolite powder mesh 50 at 1000 rpm for 30 to 40 minutes, resulting in a 21.95% reduction, reaching 13.4%. These findings indicate that the use of muffler filters with zeolite powder can significantly reduce exhaust emissions in Yamaha Jupiter Z 110cc, contributing positively to efforts in controlling air pollution from motorized vehicles